Quasiperiodic Energy Harvesting in a Delayed Rayleigh-Duffing Oscillator Near the 3-Subharmonic Resonance - Kirrou, Ilham; Bichri, Amine; Belhaq, Mohamed (Journal of Vibration Testing and System Dynamics, 2026)
The paper studies quasiperiodic vibration-based energy harvesting in a forced and delayed Rayleigh-Duffing oscillator coupled to a piezoelectric circuit. The study focuses on the effect of the time delay on the output power performance near the subharmonic resonance of order 3. Using the multiple scales method, quasiperiodic solutions and the corresponding output powers are obtained near the subharmonic resonance. The effect of the delay parameters on the energy extraction performance is analyzed in the case where the delay is introduced either in the position, in the velocity or in both. The analytical results supported by numerical simulations showed the potential of the time delay to achieve hight quasiperiodic output power over a large bandwidth around the 3-subharmonic resonance region.